2002
DOI: 10.1111/1540-627x.00035
|View full text |Cite
|
Sign up to set email alerts
|

Why Small Firms Export: Another Look

Abstract: This article examines what factors motivate small firms to export. Specifically, this study looks at firms with 200 or fewer employees, dividing the sample into two groups: firms with 25 or fewer employees and firms with more than 25 employees. The results suggest that firms with 25 or fewer employees export for two main reasons: the firm has a unique product, and it has a technological advantage over competitors. Firms with more than 25 employees export for the above two reasons, plus two additional reasons: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 8 publications
4
33
2
Order By: Relevance
“…Mittelstaedt et al (2003) found a significant positive relationship between firm size (by employment) amongst SMEs and successful exporting (Chetty and Campbell-Hunt, 2004). Pope (2002) identified similarities in motivations for exporting activity depending on firm size in that both smaller (< 25 employees) and larger (> 25) firms were more likely to export due to a new product or technological advantage. Furthermore, Pope noted a difference in motivations to export, along with firm size, as larger firms export on a large scale, seeking cost advantages and not wanting to sacrifice opportunities, emphasizing the difference in perceived risk and potential gain between smaller and larger firms.…”
Section: Why Do Smes Internationalize?mentioning
confidence: 94%
“…Mittelstaedt et al (2003) found a significant positive relationship between firm size (by employment) amongst SMEs and successful exporting (Chetty and Campbell-Hunt, 2004). Pope (2002) identified similarities in motivations for exporting activity depending on firm size in that both smaller (< 25 employees) and larger (> 25) firms were more likely to export due to a new product or technological advantage. Furthermore, Pope noted a difference in motivations to export, along with firm size, as larger firms export on a large scale, seeking cost advantages and not wanting to sacrifice opportunities, emphasizing the difference in perceived risk and potential gain between smaller and larger firms.…”
Section: Why Do Smes Internationalize?mentioning
confidence: 94%
“…For example, many studies (Kaynak et al, 1987;Bilkey and Tesar, 1977) have cited the receipt of an unsolicited order as the reason for the first export activity of the firm. Others cited the existence of underutilised production capacity (Brooks and Rosson, 1982), uniqueness of the product or a technological advantage (Pope, 2002), and competitive domestic market (Rabino, 1980;Bilkey, 1978;Pavord and Bogart, 1975;Alexandrides, 1971) for beginning to export. Several other studies have also suggested that companies begin to export in response to environmental changes, such as declining and/or saturated demand in the home market (Kaynak et al, 1987;Rabino, 1980).…”
Section: Owners' Background and Motivesmentioning
confidence: 99%
“…In addition, Gallo and Sveen (1991) found that other factors such as, company's culture, strategy, and organisational features may hinder the internationalisation process. Several studies (Pope, 2002;Sriram et al, 1989;Ganier, 1982) have examined the extent that the level of technological superiority and R&D intensity of a product were related to a firm's internationalisation. They have suggested that small exporters are able to compete in foreign markets because of their technological capabilities.…”
Section: Firm's Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations